Correlation of Simple Laboratory Result Parameters to CTP and MELD Scores, and the Diagnostic Role of Simple Laboratory Indexes to Cirrhosis Decompensation - Dewi, Ni Nyoman Gita Kharisma; Dewi, Ni Luh Putu Yunia; Dewi, Putu Itta Sandi Lesmana; Pamungkas, Kadek Mercu Narapati; Sindhughosa, Dwijo Anargha; Mariadi, I Ketut (The Indonesian Journal of Gastroenterology, Hepatology, and Digestive Endoscopy, 2024)
BackgroundCirrhosis of the liver is a final condition of all chronic liver diseases. Liver cirrhosis is the leading cause of increasing morbidity and mortality in adults worldwide. Systemic inflammation has been suggested to play an important role in causing progressive liver damage and is one of the leading causes of compensated and decompensated liver cirrhosis.Aim of StudyEvaluate the correlation of neutrophil-lymphocyte ratio (NLR), albumin-bilirubin ratio (ABR), albumin-bilirubin score (ALBI), aspartate aminotransferase to platelet ratio (APRI), albumin-creatinine ratio (ACR), lymphocyte-monocyte ratio (LMR), de ritis ratio to the severity of liver cirrhosis as assessed by CTP score and MELD score. In addition, this study also evaluated the diagnostic ability of NLR, ABR, ALBI, APRI, ACR, LMR, de ritis ratio, and CTP and MELD scores in predicting decompensated liver cirrhosis.MethodWe conducted a cross-sectional study involving patients diagnosed with liver cirrhosis at Prof DR IGNG Ngoerah General Hospital. All patients were diagnosed based on clinical history, physical examination, and investigations. This study enrolled 96 cirrhotic patients regardless of etiology. Laboratory examination results recorded platelets, neutrophils, lymphocytes, monocytes, AST, ALT, albumin, and creatinine. Then NLR, ACR, APRI, LMR, de raitis, ALBI, and ABR are calculated. CTP and MELD scores were calculated by taking data from the patient's medical recordResultOf the 96 patients tested in our study, the majority were male (66). The study found a significant moderate to very strong relationship to the MELD score between ACR, APRI, ALBI, ABR, LMR, WBC, sodium, and albumin. Neutrophil to lymphocyte ratio, ACR, De ritis, APRI, LMR, ALBI, ABR, sodium levels, and albumin have a moderate to very strong significant relationship to CTP score. ACR, De ritis, APRI, LMR, ALBI, ABR, WBC, sodium, and albumin levels with respective cut-offs £ 3.6; ≥ 1.5; ≥ 0.3; £ 2.8; ≥ 0.7; £1.6; ≥ 6.7, £ 136.50, and £ 3.0 can be used to help predict decompensated cirrhosisConclusionIn addition to using the CTP score and MELD score as a tool to predict the severity of liver cirrhosis, data from laboratory examination results in the form of albumin and ABR levels can help establish the diagnosis of decompensated cirrhosis. The sensitivity and specificity of ABR were 96.8% and 75.4% with a cut-off of £  1.6, while albumin levels were 93.5% and 81.5% with an amount off of £  3.0.